A escritura de Michel Leiris como uma interrogaçãosobre as formulações da letra em Jacques Lacan: escrita e lalíngua - Marcelo Matta de Castro (2006)
The written work by Michel Leris presents an important questioning about some concepts related to the Lacanian clinic. In this work, both the concept of letter and the notion of lalangue are approached from the questions provoked by the writing of Leris, which is composed by an intense word game, producing a deep disturbing of the language.